2021
DOI: 10.1111/nyas.14679
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: CircRNA_103948 inhibits autophagy in colorectal cancer in a ceRNA manner

Abstract: Circular RNA (circRNA) is implicated in many types of cancer; however, the expression and role of circRNAs in colorectal cancer (CRC) remains poorly understood. In this study, a circRNA microarray assay was performed to detect abnormally expressed circRNAs in CRC, and tissue arrays were used to determine the prognosis for CRC patients. Cell counting kit‐8, clone formation, wound healing, and transwell assays were used to evaluate cell functions in vitro, and a mouse subcutaneous tumor model was designed for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Therefore, circRNAs released from brain and nerve tissue lesions can be detected in peripheral blood, potentially serving as a novel biomarker to assist in the diagnosis of PD. More interestingly, increasing evidence has shown that circRNAs can act as molecular sponges of microRNAs (miRNAs) through the competing endogenous RNA (ceRNA) mechanism and competitively bind to miRNAs to alleviate miRNA inhibition [ [11] , [12] , [13] ]. Therefore, further exploration of the molecular mechanism of circRNA involvement in PD is conducive to better understanding the pathogenesis of PD and developing therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, circRNAs released from brain and nerve tissue lesions can be detected in peripheral blood, potentially serving as a novel biomarker to assist in the diagnosis of PD. More interestingly, increasing evidence has shown that circRNAs can act as molecular sponges of microRNAs (miRNAs) through the competing endogenous RNA (ceRNA) mechanism and competitively bind to miRNAs to alleviate miRNA inhibition [ [11] , [12] , [13] ]. Therefore, further exploration of the molecular mechanism of circRNA involvement in PD is conducive to better understanding the pathogenesis of PD and developing therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Related research found that circ0000069 promotes the proliferation, invasion, and migration of CRC cells and was associated with age, lymph node metastasis, and TNM staging in patients with CRC [ 20 ]. He et al found that circRNA_103948 regulates the autophagy of colorectal cancer cells through the miR-1236-3p/TPT1 axis and affects the progression of CRC [ 21 ]. In addition, studies have found that Circ-GALNT16 inhibits the progression of CRC by regulating the sequence-specific DNA binding capacity of the hnRNPK-p53 transcription complex mediated by SENP2 to inhibit Serpine1 expression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…After discarding crystal violet staining solution, cells were washed with distilled water. The colony number in each well was determined using an inverted microscope at × 40 magnification (Zeiss, Oberkochen, Germany) [ 21 ].…”
Section: Colony Formation Assaysmentioning
confidence: 99%